ROLE OF TRAUMA COUNSELLING IN SUPPORTING POLICEMEN IN NIGERIA - JIBRIL, Nadikko B. (Journal of Professional Counselling, 2025)
This study investigated the relationship among test anxiety, reading comprehension and academic performance of senior secondary school students in Gombe Local Government Area. The study adopted the correlation research design, the population of this study consisted of all 17 public senior secondary schools’ students in Gombe Local Government Area, the sample of the study are three hundred and thirty-three students (333) drawn out of a population of seven thousand two hundred and sixty-six students (7,266). Simple random sampling technique was used in selecting both the five (5) schools and the students within Gombe Local Government Area of Gombe state. Study adapted the version of test anxiety inventory questionnaire (TAI) developed by spielberger with the reliability coefficient of 0.821and reading comprehension test instrument with reliability of 0.861 and student’s terminal scores in English language was used in collecting the data. The research question was analyzed using frequency counts and percentages, research hypotheses 1 and 2 was analyzed using Pearson product moment correlation (P.P.M.C.) and research hypothesis 3 was analyzed by using multiple regressions The findings of the study revealed that there is a negative significant relationship among test anxiety, reading comprehension and academic performance among SSS students in Gombe L.G.A, and males had slightly higher than females in relation to test anxiety, reading comprehension and academic performance. It was recommended that educational psychologist, counsellors, and teachers should guide students for test and teach them techniques of tackling test anxiety and improving reading comprehension, as this efforts can build confidence in the students and to courageously face test without much fear.